Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1177/0267323105064044
|View full text |Cite
|
Sign up to set email alerts
|

Is There a European Public Sphere?

Abstract: Recently, it has been argued that, despite the absence of European-wide mass media, a European public sphere is emerging, as some issues of European relevance become debated at the same time with the same intensity and with recourse to the structures of meaning throughout the entire European Union. This article examines the media framing of Silvio Berlusconi's controversial address as president of the European Council of Ministers to the European Parliament on 2 July 2003, in which he compared the Social Democ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 11 publications
0
27
0
1
Order By: Relevance
“…Doing so helps such individuals to overcome a feeling of isolation (Greenwood and Long 2009) and continue to be involved in the life of those whom they left. Research also shows that media consumption has the ability to develop a sense of community (Downey and Koenig 2006) and hand in hand with the social media they encourage social integration, affording diffusion of information and knowledge about values, meanings, and identity. They also support linguistic preservation, communicative competence and the reduction of loneliness aroused by social distances (Arnold and Schneider 2007).…”
Section: New Media Consumption In Light Of the Structural-functional mentioning
confidence: 99%
See 1 more Smart Citation
“…Doing so helps such individuals to overcome a feeling of isolation (Greenwood and Long 2009) and continue to be involved in the life of those whom they left. Research also shows that media consumption has the ability to develop a sense of community (Downey and Koenig 2006) and hand in hand with the social media they encourage social integration, affording diffusion of information and knowledge about values, meanings, and identity. They also support linguistic preservation, communicative competence and the reduction of loneliness aroused by social distances (Arnold and Schneider 2007).…”
Section: New Media Consumption In Light Of the Structural-functional mentioning
confidence: 99%
“…But today we generate information at a faster rate than we are able to consume it. This situation has been called "infoglu," "data smog" or "information overload," and its implications are that a sense of pressure is engendered that can influence the work quality of individuals and organizations (Hahn, Lawson and Lee 1992;Shenk 1997;Eppler and Mengis 2004;McShane and Von Glinow 2005;Thomas et al 2006). If so, it is suggested that cutting off allow individuals to recover a bit from the amount of data engulfing them, to rest by taking time out, and then to "plug themselves back in" to the media flow.…”
mentioning
confidence: 99%
“…As a consequence, the recent literature has become more empirically-oriented and has focused on media coverage to establish the degree of Europeanisation of public communication over time and/or across Downloaded by [Australian National University] at 21:43 04 June 2016 countries. Many of these studies have narrowed down their analysis on public debates about specifi c European issues at given points in time -cases in point are, for instance, the Haider debate (Berkel 2006;van de Steeg 2006), EU Eastern enlargement in general (Adam 2007;van de Steeg 2002) and Turkish EU accession in particular (Wimmel 2004), the EU constitution (Adam 2007), EU summits (Meyer 2010), the EU Commission's corruption scandal (Trenz 2000), or the BerlusconiSchulz case (Downey and Koenig 2006) -but two recent large-scale collaborative research projects have off ered a cross-sectional and longitudinal examination of the overall paĴ erns of public communication in the national media (Wessler et al 2008;Koopmans and Statham 2010a). 2 Despite this impressive accumulation of empirical evidence over the last years, there remains disagreement on how to measure Europeanised communication in the various national public spheres.…”
Section: In Search Of a European Public Spherementioning
confidence: 99%
“…The study by Downey and König (2006) indicates that even if there is an obvious European reference, such as in the Berlusconi-Schulz case, similar framing of events does not occur in a way that would encourage deliberation among citizens, since the actors involved in the conflict are portrayed as representatives of ethnic nations Living Reviews in European Governance http://www.livingreviews.org/lreg-2009-2 rather than their respective political parties. Consequently, ethnicity shows more perseverance than expected, and makes deliberative change of opinion due to communication difficulties (Downey and König 2006: 165-187).…”
Section: Collective Identity Legitimacy and The European Public Spacementioning
confidence: 99%